Acompanhamento terapêutico: operadores psicanalíticos para uma clínica em movimento - Júlia Roberta de Oliveira Carvalho Caetano (2018)
This study has as goal to analyze which clinical operators Therapeutic Accompaniment could afford in its practice in the face ofpsychoses, once this practice is affected by the contingency and the open sky clinic. The encounter with psychoanalysis is the guiding principle for our research, because from this theoretical and practical referential we will be able to circumscribe our study goal and research problem. To wage this study is necessary to pass through the history of madness, to understand which positions have been occupied by the madman in society, what includes the enigma and the enclosure. The role of scientific discourse is striking, in imprinting the segregationist discourse that the madman has nothing to say. Only with the Psychiatric Reform, the crazy could have its own liberty, what includes the treatment. With the Psychiatric Reform, arises the Therapeutic Accompaniment in the ‘60s, in Argentina. This practice develops as it leaves the patient's follow-up in the hospital space, to accompany him on the street, in the wandering through the territory. We then have a practice marked by contingency, from the treatment performed in the outdoor environment, in addition to the controlled environment of the hospitals. This knowledge, which he says on a case-by-case basis, does not prevent us from thinking of a formalization to support a clinical practice. For this reason, we focus precisely on some concepts and constructions of the psychoses clinic, which finds since Freud the main characteristic of hearing the subject's word with mental suffering. From the development of the psychosis clinic and the elaborations on the treatment of the Other, the diagnosis of discourse and the construction of the clinical case, as well as other elaborations and clinical operators that concern the practice of psychoanalysis in the institutions, the emphasis is on the unique solution that each subject builds in the social bond. These elaborations will help us to analyze how the Sinthome, conceptualized by Lacan in his last teaching, can be a clinical operator for the TA, so that one can understand the subjective solutions that each subject finds out and constructs in his arrangement, in its encounter with the Other. Some clinical fragments will be analyzed from these operators, where the TA finds a practice subsidized by a theoretical contribution that emphasizes the listening of the subject.